2018
DOI: 10.1158/1078-0432.ccr-17-2041
|View full text |Cite
|
Sign up to set email alerts
|

Regional Delivery of Chimeric Antigen Receptor–Engineered T Cells Effectively Targets HER2+ Breast Cancer Metastasis to the Brain

Abstract: Purpose: Metastasis to the brain from breast cancer remains a significant clinical challenge, and may be targeted with CAR-based immunotherapy. CAR design optimization for solid tumors is crucial due to the absence of truly restricted antigen expression and potential safety concerns with “on-target off-tumor” activity. Here, we have optimized HER2-CAR T cells for the treatment of breast to brain metastases, and determined optimal second-generation CAR design and route of administration for xenograft mouse mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
200
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(203 citation statements)
references
References 32 publications
3
200
0
Order By: Relevance
“…Studies comparing routes of delivery for both preclinical models of GBM and breast cancer brain metastases have shown that local delivery (ICT or ICV) outperforms systemic delivery (IV) of CAR T cells. HER2‐CAR T cells (0.5 M dose) delivered ICV was more effective than a 10‐fold higher dose (5 M dose) delivered IV in orthotopic models of breast cancer brain metastases . Similarly, ICT administered IL13Rα2‐CAR T cells resulted in long‐term survival in orthotopic GBM models, whereas IV delivery provided no significant benefit over mock transduced T cells .…”
Section: Getting Cars To Go: Car T Cell Trafficking To Brain Tumorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Studies comparing routes of delivery for both preclinical models of GBM and breast cancer brain metastases have shown that local delivery (ICT or ICV) outperforms systemic delivery (IV) of CAR T cells. HER2‐CAR T cells (0.5 M dose) delivered ICV was more effective than a 10‐fold higher dose (5 M dose) delivered IV in orthotopic models of breast cancer brain metastases . Similarly, ICT administered IL13Rα2‐CAR T cells resulted in long‐term survival in orthotopic GBM models, whereas IV delivery provided no significant benefit over mock transduced T cells .…”
Section: Getting Cars To Go: Car T Cell Trafficking To Brain Tumorsmentioning
confidence: 94%
“…In studies of the HER2‐CAR design, our preclinical work demonstrated decreased cytokine production and improved anti‐tumor efficacy of 4‐1BB vs CD28 costimulation . Moreover, ICV‐delivered CAR T cells were shown to eradicate tumors implanted in both hemispheres.…”
Section: Initial Clinical Experience With Car T Cell Therapy For Gbmmentioning
confidence: 94%
See 1 more Smart Citation
“…In glioblastoma patients, the University of Pennsylvania group showed that EGFRvIII-directed CAR T cells effectively trafficked to regions of active tumor after systemic infusion (142), and Ahmed and colleagues reported clinically significant activity of HER2-specific CAR T cells in 8 out of 17 cases, including one PR and 7 persistent SD (143). Besides, local delivery showed encouraging results in this setting: in xenograft models, investigators demonstrated robust antitumor efficacy of anti-HER2 CAR T cells against medulloblastoma (144) and brain metastases of breast cancer (145) and anti-GD2 constructs were effective against midline gliomas (146). In addition, Brown and colleagues reported © 1996-2019 that IL-13Rα2-directed CAR T cells delivered via an implanted reservoir/catheter system exert a significant clinical activity in glioblastoma patients (147), including one CR (148).…”
Section: Car T Cells For Solid Tumorsmentioning
confidence: 99%
“…Recently, Nishio et al (2014) have overcome the obstacle through inoculating intratumorally with an armed oncolytic virus which effectively attracted CAR‐T cells to the tumor site. In addition, it is reported that directly intratumorally administered CAR‐T cells could generate a potent and long‐lasting antitumor immune response (Adusumilli et al, 2014; H. Liu et al, 2017; Pituch et al, 2018; Priceman et al, 2018). Several related clinical trials of intratumoral immunization are in research phase (Table 5).…”
Section: In Situ Antitumor Vaccination With Immune Cellsmentioning
confidence: 99%